The groin first approach for transcatheter aortic valve implantation: are we pushing the limits for transapical implantation? - Beller, Carsten J.; Schmack, Bastian; Seppelt, Philipp; Arif, Rawa; Bekeredjian, Raffi; Krumsdorf, Ulrike; Katus, Hugo; Karck, Matthias; Kallenbach, Klaus (Clinical research in cardiology, 2013)
ObjectiveTranscatheter aortic valve implantation (TAVI) is a therapeutic option for old and multimorbid patients with severe aortic stenosis. When applying the groin first approach by transfemoral implantation, patients in the transapical group are highly selected with even higher morbidity. We report outcome of the transapical group.MethodsBetween April 2008 and May 2011, 267 patients underwent TAVI through either a transfemoral (n = 201 CoreValve, n = 33 Edwards Sapien prostheses; mean age 81 ± 6 years, logistic EuroSCORE 19.5 ± 12.6 %; 4-76, STS score 7.2 ± 4 %; 1.5-28.9) or transapical approach (n = 33 Edwards Sapien prostheses; mean age 80 ± 1 years, logistic EuroSCORE 31.6 ± 17.1 %; 9.4-69.1, STS score 12.8 ± 7.1 %; 2.5-28.8). The transapical access was chosen only when transfemoral implantation was not possible.ResultsEuroSCORE and STS score were significantly higher in the transapical group (p = 0.001, respectively). A 30-day survival was comparable with 87.9 % in the transapical versus 92 % in the transfemoral group (p = 0.52). In the transapical group, female gender was predominant (n = 23; 70 %). Eight patients underwent previous cardiac surgery. All transapical implantations were successful. No bleeding or neurological complications occurred. Six patients required postoperative pacemaker implantation. Cardiac decompensation with concomitant pneumonia was the underlying cause for early mortality, except for one patient with abdominal malperfusion. Follow-up (0-37 months) was complete in 100 %, nine patients died after 30 days postoperatively (6 cardiac and 3 non-cardiac related). Echocardiography revealed good valve function with not more than mild paravalvular incompetence.ConclusionsGroin first approach is reasonable due to less invasive implantation technique. However, despite even higher predicted mortality, transapical aortic valve implantation is non-inferior to transfemoral approach.
Gesehen am 13.07.2018
Published online: 5 August 2012